Silica Support‐Enhanced Pd‐Catalyzed Allylation Using Allylic Alcohols. Issue 20 (3rd September 2018) - Motokura, Ken; Ikeda, Marika; Kim, Minjune; Nakajima, Kiyotaka; Kawashima, Sae; Nambo, Masayuki; Chun, Wang‐Jae; Tanaka, Shinji
Abstract: Although allylation using allylic alcohol is an environmentally‐friendly method because of water being the sole byproduct in such reactions, allylic alcohol is one of the most difficult allylating agents in Pd‐catalyzed allylation of nucleophiles. In this study, we successfully developed a mesoporous silica‐supported Pd complex as an efficient catalyst for the allylation of nucleophiles using allylic alcohols as allylating agents. The allylic alcohol is activated by the silanol group on the support surface, which easily undergoes a π‐allylpalladium intermediate formation. The catalytic activity of the supported Pd complex was ca. 9 times higher than that of its homogeneous precursor Pd complex. A highest turnover number of 4500 based on Pd was achieved. Various nucleophiles and allylic alcohol derivatives could be used as substrates. Not only the detailed catalyst structure but also the reaction mechanism including the concerted activation of allylic alcohol by the Pd complex and silanol were investigated by several spectroscopic techniques, such as Pd K‐edge XAFS, solid‐state NMR, and in‐situ FT‐IR measurements. Abstract : Pd does it again : Pd‐catalyzed allylation with allylic alcohol is accelerated by silanol on support surface. The catalytic activity of the supported Pd complex was ca . 9 times higher than that of its homogeneous precursor Pd complex. A highest turnover number of 4500 based on Pd was achieved.